2014
DOI: 10.1111/acps.12319
|View full text |Cite
|
Sign up to set email alerts
|

Non‐verbal communication in meetings of psychiatrists and patients with schizophrenia

Abstract: Lavelle M, Dimic S, Wildgrube C, McCabe R, Priebe S. Non-verbal communication in meetings of psychiatrists and patients with schizophrenia.Objective: Recent evidence found that patients with schizophrenia display non-verbal behaviour designed to avoid social engagement during the opening moments of their meetings with psychiatrists. This study aimed to replicate, and build on, this finding, assessing the nonverbal behaviour of patients and psychiatrists during meetings, exploring changes over time and its asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 26 publications
2
14
0
Order By: Relevance
“…The results support past findings on the importance of prosocial and flight behaviours with strengthened methodology [9,11,28]. However, in contrast to some past findings, associations with non-verbal behaviour were only found with negative symptoms and not with other symptom domains.…”
Section: Comparison With the Literaturesupporting
confidence: 85%
See 1 more Smart Citation
“…The results support past findings on the importance of prosocial and flight behaviours with strengthened methodology [9,11,28]. However, in contrast to some past findings, associations with non-verbal behaviour were only found with negative symptoms and not with other symptom domains.…”
Section: Comparison With the Literaturesupporting
confidence: 85%
“…In total, six 30-s sections were analysed for each patient, totalling 3 min. The end of each 30-s section was marked with a beep, and raters recorded the frequency of the behaviours using a 3-point scoring system, as previously used in two studies [11,28] (0 = behaviour not present, 1 = behaviour present at least once, and 2 = behaviour present more than once). A 3-point scoring system was used to capture a greater variance of behaviours, in contrast to the onezero sampling method applied in previous studies.…”
Section: Sociodemographic Informationmentioning
confidence: 99%
“…Subsequently, building an automatic and reliable AUs detection system will offer a powerful tool for different fields (e.g. Psychological field [6], [16]), that use manual annotation for studying facial behaviour. Moreover, it will have a great impact on the current challenging facial-based applications (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Third, different studies report a correlation, albeit sometimes negative, between NVB and classical measures of negative symptoms. It has been observed that patients with a predominance of these symptoms also express an overall reduction of NVB (Brüne, Abdel‐Hamid, Sonntag, Lehmkämper, & Langdon, ; Brüne et al, ; Troisi, Spalletta, & Pasini, ); this profile tends to remain stable for short periods of time, for instance during clinical consultations (Lavelle, Dimic, Wildgrube, McCabe, & Priebe, ). Assuming these evidences, several items of the assessment tool referring to specific subdomains of negative symptoms, such as blunted affect and alogia, could be analyzed within the frame of NVB.…”
Section: Introductionmentioning
confidence: 99%